Pengaruh Digital Financial Literacy, Hedonic Lifestyle, dan Self Control Terhadap Financial Well Being Melalui Impulsive Buying Behavior Sebagai Variabel Mediasi (Studi pada Generasi Z Pengguna Paylater di Kota Pasuruan) - Mukhammad Ali Saputra; Any Urwatul Wusko (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
The rapid development of digital financial technology has transformed consumer spending behavior, particularly among Generation Z, which is recognized as the most active group in utilizing financial technology services. One of the most widely used services is PayLater, which offers greater convenience in conducting financial transactions but may also influence individuals' financial well-being through impulsive buying behavior. This study aims to examine the effects of Digital Financial Literacy, Hedonic Lifestyle, and Self Control on Financial Well-Being, with Impulsive Buying Behavior serving as a mediating variable among Generation Z PayLater users in Pasuruan City This study employed a quantitative research approach using a purposive sampling technique. The respondents consisted of 385 Generation Z PayLater users residing in Pasuruan City. Data were collected through an online questionnaire using a Likert scale. The data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4.0 software The findings indicate that Digital Financial Literacy, Hedonic Lifestyle, and Self Control have a positive and significant effect on both Financial Well-Being and Impulsive Buying Behavior. Meanwhile, Impulsive Buying Behavior does not have a significant effect on Financial Well-Being, indicating that it does not mediate the relationship between the three independent variables and Financial Well-Being. Furthermore, the proposed research model explains 52.6% of the variance in Financial Well-Being and 66.7% of the variance in Impulsive Buying Behavior.